2021
DOI: 10.1093/cid/ciab910
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Applicability of Rapid Diagnostic Testing in Antimicrobial Stewardship in the Asia-Pacific Region: A Delphi Consensus

Abstract: Rapid diagnostic tests (RDTs) facilitate fast and accurate identification of infectious disease microorganisms and are a valuable component of multimodal antimicrobial stewardship (AMS) programs, but are currently underutilized in Asia Pacific. An experienced group of infectious diseases clinicians, clinical microbiologists and a clinical pharmacist used a modified Delphi consensus approach to construct 10 statements aiming to optimize the utility and applicability of infection-related RDTs for AMS in the Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…To explore the value and impact of RDTs within an ASP, one must first consider the global definition of an RDT. The EWG agreed that a wide range of definitions exist for ‘rapid’, varying from 90 min up to 24 h. According to a Delphi Consensus in Asia–Pacific, RDTs should provide results within 4–6 h to determine treatment before administration of the second dose of an antimicrobial [ 18 ]. To accommodate a variety of settings, where this is not possible delivery of results within 24 h may be acceptable [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the value and impact of RDTs within an ASP, one must first consider the global definition of an RDT. The EWG agreed that a wide range of definitions exist for ‘rapid’, varying from 90 min up to 24 h. According to a Delphi Consensus in Asia–Pacific, RDTs should provide results within 4–6 h to determine treatment before administration of the second dose of an antimicrobial [ 18 ]. To accommodate a variety of settings, where this is not possible delivery of results within 24 h may be acceptable [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…To achieve optimal antimicrobial use, RDTs must be used to facilitate decision-making at various stages of the clinical pathway, i.e. antimicrobial initiation, on-treatment, and de-escalation [ 18 ]. Use of RDTs as part of bundled interventions that support decision-making is key.…”
Section: Effective Implementation Is Key To Realise the Value Of Rdts...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the hospital level, the development of rapid molecular techniques now allows for rapid de-escalation strategies or even immediate documented treatment, making it possible to spare broad-spectrum molecules [ 50 , 51 ]. Abbara and colleagues showed that an antibiotic stewardship program promoting a strategy of systematic de-escalation associated with restricted use of molecules with a high ecological impact made it possible to achieve a lasting drop in the resistance rate of Pseudomonas aeruginosa in an intensive care unit.…”
Section: Resultsmentioning
confidence: 99%
“…Selecting the appropriate test can be particularly difficult when the clinical presentation overlaps several etiologies. Rapid molecular diagnostics, generally defined as providing a result within 4–6 h, that test for a range of potential pathogens are becoming increasingly ubiquitous and offer much promise for improving outcomes [ 11 ]. These panels testing for multiple pathogens with a single test have improved diagnostic yield compared to the standard of care where one to many individual tests are ordered.…”
Section: Considerations For Pre-analytical Diagnostic Stewardship Int...mentioning
confidence: 99%